DINAMIKA DAN NYALA API PEMBAKARAN DROPLET CAMPURAN METIL LAURAT – METIL OLEAT - Yuliati, Lilis; Hamidi , Nurkholis; Lazuardi, Muhamad Luthfi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
This research intended to investigate the dynamics and flame of the droplet combustion of methyl laurate - methyl oleate blended. Methyl oleate is an unsaturated FAME with a relatively long carbon chain, frequently found as the dominant component in various biodiesel. Meanwhile, methyl laurate is a saturated FAME with a shorter carbon chain, which is the main component in coconut oil biodiesel. The methyl oleate content in the droplets was varied by 0, 20, 40, 60, 80, and 100%. Visual observations and temperature measurements were conducted on the combustion of suspended droplets with a diameter of 1.24 mm. The droplet is supported by a thermocouple junction with a wire diameter of 0.1 mm. The experimental results show that increasing of the methyl oleate content increase the ignition delay time, burning time, thermal expansion of droplets as well as fluctuations in droplet diameter and combustion temperature. Ignition delay time has a much greater value than burning time. This parameter should be suppressed to obtain more complete combustion and cleaner exhaust emissions, especially in internal compression engine applications where the time available for the combustion process is very short. This can be obtained by increasing the percentage of methyl laurate in biodiesel.